Hemodialysis Treatment Time: As Important as it Seems?. Issue 2 (16th January 2017) - Daugirdas, John T.
Abstract: Hemodialysis treatment time and Kt / V can both be considered to be primary measures of hemodialysis adequacy, because when either goes to zero, mortality is certain in patients without residual kidney function. Treatment time is important, but it needs to be adjusted based on surface‐area‐normalized Kt/V, residual kidney function, and expected ultrafiltration rate. Rescaling dose of dialysis measured as Kt/V to body surface area prevents ultrashort dialysis in small patients, women, and children with minimal residual kidney function. Most if not all of the observational studies of associations between outcome and dialysis session length are probably confounded by dose targeting bias. Once adequate Kt/V (taking into account body surface area) has been provided, adequate dialysis time probably is most relevant in terms of limiting the need for a high fluid removal rate. The latter may adversely impact survival by causing recurrent ischemia to cardiovascular and other tissues. There is little high‐quality evidence at this time to support a minimum 4‐hour treatment time for all patients, regardless of body size, solute removal, or residual kidney function. On the other hand, there is little evidence that prolonging weekly treatment time up to 24 hours per week is harmful. The final decision regarding treatment time is best individualized, based on patient acceptability and experience, residual kidney function, body surface‐area‐normalized Kt/V, and expected ultrafiltration rate.